2002
DOI: 10.1128/cmr.15.4.595-612.2002
|View full text |Cite|
|
Sign up to set email alerts
|

History of Human Parasitology

Abstract: Humans are hosts to nearly 300 species of parasitic worms and over 70 species of protozoa, some derived from our primate ancestors and some acquired from the animals we have domesticated or come in contact with during our relatively short history on Earth. Our knowledge of parasitic infections extends into antiquity, and descriptions of parasites and parasitic infections are found in the earliest writings and have been confirmed by the finding of parasites in archaeological material. The systematic study of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
0
30

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(206 citation statements)
references
References 122 publications
1
175
0
30
Order By: Relevance
“…5.165). [416,417] Evidence of diseases marked by periodic (tertian or quartan) fever [418] attacks is also provided by Indian traditional medicines (Ayurveda). Already the oldest reference texts, like the Charaka Samhita, distunguish between fever episodes recurring every third or fourth day (caused by Plasmodium vivax or Plasmodium ovale (malaria tertiana), and respectively by Plasmodium malariae (malaria quartana)).…”
Section: Mosquito In Amber From a Mine Near The Northern Cordillera Smentioning
confidence: 99%
“…5.165). [416,417] Evidence of diseases marked by periodic (tertian or quartan) fever [418] attacks is also provided by Indian traditional medicines (Ayurveda). Already the oldest reference texts, like the Charaka Samhita, distunguish between fever episodes recurring every third or fourth day (caused by Plasmodium vivax or Plasmodium ovale (malaria tertiana), and respectively by Plasmodium malariae (malaria quartana)).…”
Section: Mosquito In Amber From a Mine Near The Northern Cordillera Smentioning
confidence: 99%
“…In diesem Buch werden epidemisch auftretende, paroxysmale (anfallsartige) Fiebererkrankungen in Verbindung mit der Vergrößerung der Milz beschrieben, die als Plasmodium vivax-oder Plasmodium malariae-Infektionen gedeutet werden können [8].…”
Section: Die Geschichte Der Krankheitunclassified
“…2 The trypanosomes had been first reported to occur in trouts (Valentine, 1841) and frogs (Gluge, 1842), 3 but it was not until 1881 that Griffith Evans found trypanosomes in the blood of horses and camels with a wasting disease called Surra and suggested that the parasites might be the cause of this disease. 4 In 1895, the Scottish Pathologist and Microbiologist David Bruce discovered Trypanosoma brucei as the cause of cattle nagana (cattle Trypanosomiasis). 5 Surra is widespread in different parts of the world and poses a major constraint to camel productivity.…”
Section: Introductionmentioning
confidence: 99%